The impacts of hypertonic conditions on Drosophila larval cool cells - Bai, Hua; Naidu, Trisha; Anderson, James B.; Montemayor, Hector; Do, Camie; Ni, Lina (Frontiers in Cellular Neuroscience, 2024)
Drosophila melanogaster exhibits multiple highly sophisticated temperature-sensing systems, enabling its effective response and navigation to temperature changes. Previous research has identified three dorsal organ cool cells (DOCCs) in fly larvae, consisting of two A-type and one B-type cell with distinct calcium dynamics. When subjected to hypertonic conditions, calcium imaging shows that Atype DOCCs maintain their responses to cool temperatures. In contrast, a subset of B-type DOCCs does not exhibit detectable GCaMP baseline signals, and the remaining detectable B-type DOCCs exhibit reduced temperature responses. The activation of both A-type and B-type DOCCs depends on the same members of the ionotropic receptor (IR) family: IR21a, IR93a, and IR25a. A-type DOCCs exhibit a higher somal level of IR93a than B-type DOCCs. Overexpression of Ir93a restores B-type calcium responses to cool temperatures, but not the proportion of B-type cells with a detectable GCaMP baseline, in a hypertonic environment, suggesting a selective role of IR93a in maintaining the temperature responses under hypertonic conditions. Our findings identify a novel function of B-type DOCCs in integrating temperature and tonic stimuli.